Insights into the Dynamics of History: A Glow after Memory of a Postcolonial World inV.S.Naipaul’sThe Mimic Men - Mzoughi, Imen (International Journal of Psychosocial Rehabilitation, 2024)
V.S.Naipaul’s longing for a great Caribbeanarchipelago within the scope of his novelentitledThe Mimic Men is praiseworthy. Naipaul is a Trinidadian writer stationed in Britain.He was educated in England. His novel The Mimic Men (1967) is a vivid account of thedifferent influences shaping the Caribbean community and individuals. His book invokes apersonal journey cast through the character of Singh. The protagonist is the archetype of acritical criollist. The granted awards to Naipaul testify to his genius in adopting and adaptinghis narrative to accentuate the multi-culturality of the Caribbean.Naipaul belongs to theBlack Caribbean diaspora. Yet, he has been stationed in different metropolitan centres.Hisliterary outputs thus match his existential predicament.As a black Caribbeanwriter,Naipaul embodies both first and third world sensibilities. He can speak on behalf ofdiasporic identities. The composite of his inclusive representations of Caribbeans finds itselfexpressed in a nostalgic discourse for a great Caribbean archipelago. Impelled by a growingdesire to delineate the features of a Caribbean identity which defies easy categorizations, thispaperestablishes a cultural identity for Caribbeanswithout imposing any restricted definitionof identity.Also, this paper strives to rewrite the theory of postcolonialism in an endeavour tomeet the complexity of the Caribbean archipelago and the identity of its inhabitants.